The Influence of The Social Environment on Student Learning Outcomes at Nagasari III Elementary School - Sarah Nur Aqila; Linda Riski Sefrina; Milliyantri Elvandari (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2024)
Background: Student learning outcomes are one of the main indicators of the success of an education. Environment is a factor that affects the growth and development of living things. There are three places within the scope of the social environment, namely the family environment, the school environment, and the community environment. Research Metodes: This research design uses cross-sectional with a sample of 35 respondents. Data analysis used Spearman's rho test and t test, to determine the correlation of variables and significant influence. Results: There is no significant relationship between the two variables with a significant value (0.242 < 0.05). And there is no influence on the two variables with the value of tcount < ttable (-1.193 < 2.034). Conclusion: There is no significant relationship and influence between social environment and student learning outcomes.